Protective Settlement Procedures in Kuwaiti Law 71 (2020): A Comparative Study of Islamic Jurisprudence - Alajmi , Abdulhadi M A; Mansour , Mohammad Khalid (Dirasat: Shari'a and Law Sciences, 2023)
Objectives: This research aims to study the most prominent legal procedures related to the preventive settlement system in the Kuwaiti Bankruptcy Law (2020), compare it with the previous law contained in the canceled articles (555-800) of the Kuwaiti Trade Law 68 (1980), explain Islamic jurisprudence perspective on these procedures. It also aim to create a comparison between law and Islamic jurisprudence. Methods: The researcher studied issues related to debtor's contracts at the initiation of the preventive settlement procedures, such as debt deadlines, their validity, debtor's access to new financing, and majority requirement for approval of the preventive settlement proposal. To clarify this, the researcher used an inductive approach, deductive approach, and comparative approach. Results: The research concluded that many procedures contained in the current Law 71 (2020) were not included in the repealing articles regulating bankruptcy in Kuwait Trade Law 68 (2020), and some legal procedures related to the preventive settlement system are compatible with Islamic jurisprudence, while others are not. The ruling sometimes differs according to the condition of the debtor, whether he is bankrupt, his debts have exceeded his funds, or he is facing financial default and has not entered the stage of bankruptcy. Conclusions: The study sees the need to amend some articles of the Kuwaiti Bankruptcy Law (2020) related to the preventive settlement system to comply with Islamic jurisprudence, especially since this system has a major role in preventing the debtor from falling into bankruptcy and protecting commercial entities.